Design of a load module payment in public entities through messaging with spring framework - Santos López, Félix Melchor (2012)
Public entities and institutions in Peru offer several services to citizens, where there are payments and financial transactions. Therefore, an important process called “payment accreditation” is necessary when a bank send public entities all the transactions, in a file, made by Internet and bank counters during a day, then these are registered as valid. The main solution presented in this article is the implementation of a task-scheduler and a register payment application, which were developed under Java language programming, Spring Framework, JMS (Java Message Service) and a Message Broker. As a result, the solution produced a great design for information system because UML was applied, also a right software architecture and its accurate documentation for further maintenances.